Update on LIPID MAPS classification, nomenclature, and shorthand notation for MS-derived lipid structures - Liebisch, Gerhard; Fahy, Eoin; Aoki, Junken; Dennis, Edward A; Durand, Thierry; Ejsing, Christer S; Fedorova, Maria; Feussner, Ivo; Griffiths, William J; Köfeler, Harald; Merrill, Jr, Alfred H; Murphy, Robert C; et al. (Journal of lipid research, 2020)
A comprehensive and standardized system to report lipid structures analyzed by MS is essential for the communication and storage of lipidomics data. Herein, an update on both the LIPID MAPS classification system and shorthand notation of lipid structures is presented for lipid categories Fatty Acyls (FA), Glycerolipids (GL), Glycerophospholipids (GP), Sphingolipids (SP), and Sterols (ST). With its major changes, i.e., annotation of ring double bond equivalents and number of oxygens, the updated shorthand notation facilitates reporting of newly delineated oxygenated lipid species as well. For standardized reporting in lipidomics, the hierarchical architecture of shorthand notation reflects the diverse structural resolution powers provided by mass spectrometric assays. Moreover, shorthand notation is expanded beyond mammalian phyla to lipids from plant and yeast phyla. Finally, annotation of atoms is included for the use of stable isotope-labeled compounds in metabolic labeling experiments or as internal standards. This update on lipid classification, nomenclature, and shorthand annotation for lipid mass spectra is considered a standard for lipid data presentation.